Healing and cytotoxic effects of Psidium guajava (Myrtaceae) leaf extracts - Kristianne Porta Santos Fernandes; Sandra Kalil Bussadori; Márcia Martins Marques; Nilsa Sumie Yamashita Wadt; Erna Bach; Manoela Domingues Martins (Universidade Estadual de Campinas, 2015)
Aim: The aims of this study were to evaluate the wound healing potential in vivo and the cytotoxic effects in vitro of Psidium guajava (Myrtaceae) leaf extract and commonly used corticosteroids. Methods: The healing effect was studied in vivo by the clinical and histological evaluation of traumatic lesions in the oral mucosa of rats treated with these substances. Each rat received 2 daily applications of the medicine tested and the animals were sacrificed after 1, 3, 5, 7 and 14 days. Tissue sections stained with hematoxylin & eosin were analyzed. The histological evaluation involved a 5-point scoring system based on the degree of healing, ranging from 1 (total repair of epithelium and connective tissue) to 5 (epithelial ulcer and acute inflammatory infiltrate). The Kruskal-Wallis test was used for statistical analysis of the histological scores. For the in vitro toxicity assay, each substance was applied to mucosa fibroblast cell cultures in conditioned media. The media were conditioned by placing the substances in contact with fresh culture medium for 24 h. The cytotoxicity analysis was performed using the MTT assay. Data were analyzed statistically by ANOVA and Tukey's test at 5% significance level. Results: In vitro, the guava extract caused a decrease in the cell viability and growth when compared to the control and corticosteroids. In vivo, guava extract caused accelerated wound healing from the 3rd day, whereas the corticosteroids delayed tissue repair and were associated with bacterial surface colonization, the presence of micro-abscesses and intense inflammatory infiltrate in the submucosa. Conclusions: Although in a short-term cytotoxicity analysis, the guava extract reduced the cell population in vitro, while in vivo, the extract accelerated wound healing.